Building Community Resiliency through Immersive Communal Extended Reality (CXR) - Sharon Yavo-Ayalon; Swapna Joshi; Yuzhen (Adam) Zhang; Ruixiang (Albert) Han; Narges Mahyar; Wendy Ju (Multimodal Technologies and Interaction, 2023)
Situated and shared experiences can motivate community members to plan shared action, promoting community engagement. We deployed and evaluated a communal extended-reality (CXR) bus tour that depicts the possible impacts of flooding and climate change. This paper describes the results of seven community engagement sessions with a total of N = 74 members of the Roosevelt Island community. We conducted pre- and post-bus tour focus groups to understand how the tour affected these community members’ awareness and motivation to take action. We found that the unique qualities of immersive, situated, and geo-located virtual reality (VR) on a bus made climate change feel real, brought the consequences of climate change closer to home, and highlighted existing community resources to address the issue. Our results showed that the CXR experience helped to simulate a physical emergency state, which empowered the community to translate feelings of hopelessness into creative and actionable ideas. Our finding exemplifies that geo-located VR on a bus can be a powerful tool to motivate innovations and collective action. Our work is a first-of-its-kind empirical contribution showing that CXR experiences can inspire action. It offers a proof-of-concept of a large-scale community engagement process featuring simulated communal experiences, leading to creative ideas for a bottom-up community resiliency plan.